Canakinumab as treatment for COVID-19-related pneumonia: A prospective case-control study - Generali, Daniele (Int J Infect Dis, 2021)
OBJECTIVES: Canakinumab is an IL-1β antibody that neutralises the activity of IL-1β. This study examined the efficacy and safety of canakinumab in patients with moderate COVID-19-related pneumonia. DESIGN: This study aimed to evaluate the reduction in duration of hospitalisation with adequate oxygen status. Forty-eight patients with moderate COVID-19-related pneumonia were asked to participate in the prospective case-control study: 33 patients (cases) signed informed consent and received canakinumab (Cohort 1) and 15 patients (Controls) refused to receive the experimental drug and received institutional standard of care (Cohort 2). RESULTS: Hospital discharge within 21 days was seen in 63% of patients in Cohort 1 vs. 0% in Cohort 2 (median 14 vs. 26 days, respectively; p < 0.001). There was significant clinical improvement in ventilation regimes following administration of canakinumab compared with Cohort 2 (Stuart-Maxwell test for paired data, p < 0.001). Patients treated with canakinumab experienced a significant increase in PaO(2):FiO(2) (p < 0.001) and reduction in lung damage by CT (p = 0.01), along with significant decreases in immune/inflammation markers that were not observed in Cohort 2. Only mild side-effects were seen in patients treated with canakinumab; survival at 60 days was 90.0% (95% CI 71.9–96.7) in patients treated with canakinumab and 73.3% (95% CI 43.6–89.1) for Cohort 2. CONCLUSIONS: Treatment with canakinumab in patients with COVID-19-related pneumonia rapidly restored normal oxygen status, decreased the need for invasive mechanical ventilation, and was associated with earlier hospital discharge and favourable prognosis versus standard of care.